The Adsorption and Separation of Ethylene, Oxygen and Carbon Dioxide Gases on Molecular Sieves - Li Defu; Wang Jinqu (Adsorption Science & Technology)
The equilibrium adsorption and diffusion properties of ethylene, oxygen and carbon dioxide gases on two kinds of molecular sieve at 25°C were measured by gravimetric methods using a Cahn-2000 electrobalance. On both molecular sieves, the equilibrium adsorption capacity of ethylene was larger than that of oxygen and close to that of carbon dioxide, indicating that it would not be possible to remove oxygen and carbon dioxide gases from their mixture with ethylene in order to effect recovery of the latter via equilibrium separation methods. However, during the early stages of adsorption, the adsorption rates of carbon dioxide and oxygen were faster than that of ethylene thereby suggesting recovery of the latter from the gaseous mixture via kinetic separation based on the difference in adsorption diffusivity. Such separation was conducted using a two-bed column pressure swing adsorption arrangement with the effects of the experimental conditions on the separation being investigated. Oxygen and carbon dioxide may be adsorbed and removed from the gaseous mixture, leaving the output gases rich in ethylene.